Quantitative proteomic analysis of cell envelope preparations under iron starvation stress in Aeromonas hydrophila. Issue 1 (December 2016) - Yao, Zujie; Wang, Zhihong; Sun, Lina; Li, Wanxin; Shi, Yan; Lin, Ling; Lin, Wenxiong; Lin, Xiangmin
Abstract Background Iron homeostasis is an essential process over the entire lives of both hosts and bacterial pathogens, and also plays roles in many other metabolic functions. Currently, knowledge is limited on the iron scavenging mechanism of the cell envelope in the aquatic pathogen, Aeromonas hydrophila . To understand the iron homeostasis mechanism inA. hydrophila, a dimethyl labelling based quantitative proteomics method was used to compare the differential expression of cell envelope proteins under iron starvation. Results A total of 542 cell envelope proteins were identified by LC-MS/MS, with 66 down-regulated and 104 up-regulated proteins. Bioinformatics analysis showed that outer membrane siderophores, heme and iron receptors, periplasmic iron binding proteins, inner membrane ABC transporters and H+ -ATP synthase subunits increased in abundance while iron-cluster proteins, electron transport chain and redox proteins were down-regulated. Further q-PCR validation, in vivo addition of exogenous metabolites, and an enzyme inhibition assay revealed that redox, the energy generation process, and ATP synthase elevated the susceptibility ofA. hydrophila to iron starvation. Conclusions Our study demonstrates that the redox and energy generation process, and ATP synthase inA. hydrophila may play critical roles in iron acquisition under conditions of iron-stress. An understanding of the iron scavenging mechanism may be helpful for the development of strategies for preventing and treatingA. hydrophila infection.